Examination and Explanation of the Model of Superior Organizational Climate for the Promotion of Knowledge in Islamic Azad Universities - Mehdizadeh Amiri, Mohammad; Shojaei, Ali Asghar; Hosseinzadeh, Babak (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The purpose of this research is to examine and explain the model of a superior organizational climate for the promotion of knowledge in the Islamic Azad Universities of Mazandaran Province. Methodology: This research is applied in terms of its objective and descriptive-survey in terms of data collection method. Data were collected using a standard researcher-made questionnaire. The statistical population comprises 1,537 faculty members from various departments of Islamic Azad Universities in Mazandaran Province. The sampling method is cluster random sampling. Initially, the entire Mazandaran Province was divided into three clusters: eastern, central, and western. From each cluster, three counties were selected, making a total of nine counties chosen as the statistical sample. Subsequently, 308 faculty members from these counties were considered. Data analysis was conducted using structural equation modeling with Smart PLS4 software. Findings: The results indicate that all indicators and factors influencing the superior organizational climate for the promotion of knowledge in Islamic Azad Universities have a factor loading greater than 0.4, thus confirming the indicators and influential factors. Furthermore, the model of factors influencing the superior organizational climate for the promotion of knowledge in Islamic Azad Universities was depicted. The impact of causal factors on the superior organizational climate within the university, and contextual and environmental factors on strategies were found to be significant. Additionally, strategies had a positive and significant impact on outcomes and results. Conclusion: The factors of the model of a superior organizational climate in universities aimed at promoting knowledge can be generally recommended as a practical and comprehensive package for all university managers and executive bodies.